Somatic Genomic Testing in Patients With Metastatic or Advanced Cancer: ASCO Provisional Clinical Opinion. Issue 11 (10th April 2022) - Chakravarty, Debyani; Johnson, Amber; Sklar, Jeffrey; Lindeman, Neal I.; Moore, Kathleen; Ganesan, Shridar; Lovly, Christine M.; Perlmutter, Jane; Gray, Stacy W.; Hwang, Jimmy; Lieu, Christopher; André, Fabrice; et al.
Abstract : PURPOSE: An ASCO provisional clinical opinion offers timely clinical direction to ASCO's membership following publication or presentation of potentially practice-changing data from major studies. This provisional clinical opinion addresses the appropriate use of tumor genomic testing in patients with metastatic or advanced solid tumors. CLINICAL CONTEXT: An increasing number of therapies are approved to treat cancers harboring specific genomic biomarkers. However, there is a lack of clarity as to when tumor genomic sequencing should be ordered, what type of assays should be performed, and how to interpret the results for treatment selection. PROVISIONAL CLINICAL OPINION: Patients with metastatic or advanced cancer should undergo genomic sequencing in a certified laboratory if the presence of one or more specific genomic alterations has regulatory approval as biomarkers to guide the use of or exclusion from certain treatments for their disease. Multigene panel–based assays should be used if more than one biomarker-linked therapy is approved for the patient's disease. Site-agnostic approvals for any cancer with a high tumor mutation burden, mismatch repair deficiency, or neurotrophic tyrosine receptor kinase ( NTRK ) fusions provide a rationale for genomic testing for all solid tumors. Multigene testing may also assist in treatment selection by identifying additional targets when there are few or no genotype-based therapy approvals for the patient's disease. For treatment planning, the clinician should consider the functional impact of the targeted alteration and expected efficacy of genomic biomarker–linked options relative to other approved or investigational treatments. Additional information is available at www.asco.org/assays-and-predictive-markers-guidelines .